The Impact of Knowledge Management Practices On The Survival and Sustenance of Construction Organisations - Onyeagam, Onyealilam; Nwaki, William; Obonadhuze, Bernard; Zakariyau, Mohammed (UI Scholars Hub, 2020)
The dynamics in technological advancement and innovations in construction methods have caused construction organizations to operate in a highly competitive environment. As knowledge is an essential asset for surviving and remaining competitive in the construction industry, this study investigates the impact of knowledge management practices on the survival and sustenance of construction organizations. Construction professionals in Abuja-Nigeria were sampled using a well-structured questionnaire and multi-sampling techniques. The results of the study show that there is a low level of implementation of Knowledge Management among the construction organizations. Furthermore, it is found that the significant benefits of KM implementation are to improve the firm's competitive position, risks reduction, and better collaboration, to encourage innovation and profitability, faster problem solving, to improve project pricing, and to improve client satisfaction and patronage. It can be concluded that KM is a tactical and strategic competitive tool for surviving high competition in the construction industry. To ensure knowledge exchange between the locals and expatriates, the government should make a 'knowledge management plan' an essential part of the contract documents for pre-qualification and selection criteria.